Konstruksi Ideologis Status Kepegawaian Dosen Di Indonesia Dalam Perspektif Analisis Wacana Kritis - M Ghufroni An'ars; Jafar Fakhrurozi; Masnia Rahayu; Try Ruliyanti (Universitas Muhammadiyah Surabaya, 2026)
This article examines the ideological construction behind the lecturer employment status categorization system in Indonesia using the Critical Discourse Analysis (CDA) framework with Ruth Wodak's Discourse-Historical Approach (DHA). Data comprise higher education regulatory texts (Law No. 14/2005 through various ministerial regulations) and community discourse from campus trade union forums. Analysis employs five DHA discursive strategies: referential, predication, argumentation, perspectivization, and intensification/mitigation. Findings reveal that the proliferation of lecturer categories, from civil servant lecturers (ASN) and permanent non-ASN lecturers, to informal labels such as dosen ngamen, dosen terbang and dosen luar biasa constitutes a discursive mechanism serving the ideological project of academic labor flexibilization. Policy texts normalize this hierarchy through mitigation and naturalization strategies, while informal community labels function paradoxically as both symbolic resistance and reproduction of precarity.